ISO 2789 and ISO 11620: Short Presentation of Standards as Reference Documents in an Assessment Process - Renard, Pierre-Yves (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
The aim of this paper is to show how international standards dealing with library statistics and indicators (ISO 2789, ISO 11620 and others projects which are still under development) can be used as reference documents and strategic tools in a performance assessment process. The task is not an easy one, because it requires linking up somewhat complex entities such as the standardization work characteristics, the capacity of statistics to account for reality and, lastly, the variety and speed of libraries’ advancement. Nevertheless, ISO 2789 (International Library Statistics) and ISO 11620 (Performance indicators for libraries), which are based on an international consensus of experts, take into account, as much as possible, the recent evolutions in library structures and services. In addition, they are related to classical and shared assessment models. So, although their aim is not to draw up an assessment framework, they reveal themselves useful for basic operations in such a framework: to define objects and services, and to classify, count and build appropriate indicators. Moreover, as the issue of quantifying and promoting intangible assets becomes a concern in the public sector, these standards can be seen as a first attempt to define library resources and services as such intangible assets. Finally, the challenge of forthcoming evolutions of these standards is the ability to stay up-to-date in a very quickly evolving context. More precisely, the increase in the usability of these standards must be based on an ongoing search for more consistent data and relevant indicators. The question of improvement of the general design of the statistics and indicators standards family should also be addressed.